Analisis Kelayakan Investasi pada Proyek Perumahan Sederhana Tipe 31/60 M2 - Soebandono, Bagus (Syntax Literate, 2024)
The need for housing is increasing along with the rate of population growth. Simple livable housing is an option for low-income communities in accordance with the regional minimum wage. In making investments to make housing requires a feasibility analysis so that it can assess in accordance with the company's financial capabilities so that the company does not experience losses and make profits after investing large enough funds. This study aims to analyze the feasibility of investing in the MPR 2 Type 31/60 m2 simple housing development project in the Semarang Regency area which is viewed from a financial perspective using the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit Cost Ratio (BCR) methods. Based on the research that has been done, it can be concluded in terms of the feasibility of investing in the construction of subsidized houses type 31/60 in MPR 2 housing is feasible. This can be seen from the results of the analysis with the positive NPV method of Rp.127,933,335.12 > 1, the results of the analysis with the IRR method of 9.79% > 5% (MARR), the results of the analysis with the PP method, it shows that the period of return on investment occurs for 1 year 4 days, and the results of the analysis with the BCR method of 1.018 > 1.